Improvement Of Digital Marketing Strategy Kickskemon Cleaning Shoe Service With Sostac Method - Arsyadi, Muhammad Giga Rizky; Wulandari, Sari; Alam, Putra Fajar (eProceedings of Engineering, 2023)
Abstrak- In this digital era, many people's activities must use digital technology, especially social media. When it’s the New normal, social media marketing is the way that is more effective in connecting with customers and helping them to aware and understand their brand of business. Kicks Kemon is one of the cleaning shoe businesses in Jakarta, and this business started in 2015, Apart from cleaning, Kicks Kemon also offer shoe care such as reglue, repainting, and cleaning g-shock watch. For 6 years various kinds of marketing methods have been done, one of which is online marketing like social media Line, Facebook, and Instagram. but we concern about promotion who do not get awareness from social media, because not paying attention to social media as a good promotion platform, so we can conclude promotion in social media is the root of why Kicks Kemon is unable to increase its sales. The second of the lowest is CleanZoneJkt which uses Instagram, Facebook, TikTok and Website. So, it’s very important to engage the customers with strategy digital marketing SOSTAC method through social marketing and customer can indirectly be aware of the brand and selling product, because now technology is developing rapidly. Keywords- marketing strategy, social media, SOSTAC, business,